Analisis Pengaruh Daya Tarik Wisata terhadap Minat Berkunjung ke Taman Nasional Bromo Tengger Semeru - Ketthy, Abel Tatia; Berutu, Feronika (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to find out whether tourist attractions influence interest in visiting Bromo Tengger Semeru National Park, and how much influence tourist attractions influence interest in visiting. The research method used in this research is quantitative research methods and sampling using 0.01 sampling on 30 respondents who know the Bromo Tengger Semeru National Park. Research techniques were processed using the SPSS application. Based on the results of this research, it is revealed that there is a positive and significant influence between tourist attraction variables on interest in visiting Bromo Tengger Semeru National Park, with a contribution of 34.1%.